Common Fixed Points of Generalized Interpolative Kannan-Meir-Keeler Pair Contraction - Verma, Rohit Kumar; Shrivas, Jaynendra; Singh, Prachi; Kuleshwari (Journal of Informatics and Mathematical Sciences, 2025)
In this paper, we introduce a generalized version of Meir-Keeler type contraction by incorporating interpolative conditions for a pair of mappings in metric spaces. We establish new common fixed point theorems that extend as well as unify several well-known results in the literature. Our findings generalize and enhance the recent results of Noorwali et al. [10].